Isolation of dental pulp stem cells with high osteogenic potential - Takazumi Yasui; Yo Mabuchi; Satoru Morikawa; Katsuhiro Onizawa; Chihiro Akazawa; Taneaki Nakagawa; Hideyuki Okano; Yumi Matsuzaki (Inflammation and Regeneration, 2017)
Abstract Dental pulp stem cells/progenitor cells (DPSCs) can be easily obtained and can have excellent proliferative and mineralization potentials. Therefore, many studies have investigated the isolation and bone formation of DPSCs. In most previous reports, human DPSCs were traditionally isolated by exploiting their ability to adhere to plastic tissue culture dishes. DPSCs isolated by plastic adherence are frequently contaminated by other cells, which limits the ability to investigate their basic biology and regenerative properties. Additionally, the proliferative and osteogenic potentials vary depending on the isolated cells. It is very difficult to obtain cells of a sufficient quality to elicit the required effect upon transplantation. Considering clinical applications, stem cells used for regenerative medicine need to be purified in order to increase the efficiency of bone regeneration, and a stable supply of these cells must be generated. Here, we review the purification of DPSCs and studies of cranio-maxillofacial bone regeneration using these cells. Additionally, we introduce the prospective isolation of DPSCs using specific cell surface markers: low-affinity nerve growth factor and thymocyte antigen 1.